Banking Associations Their Role and Impact in a Time of Market Change - Sredojevic, Sladjana (Moorad Choudhry global banking series., 2022)
Banking Associations, as business associations representing the interests of its members (banks) at the national level, in today's changing regulatory and economic environment have an increasingly important role not only in the Banking sector but in the wider economy. Their increasing importance is deriving from their mission, structure and capabilities to obtain and promote different interests in the economy and wider society. It is important to understand their mission, vision and activities and ideally to include Banking Associations in the market decision making process. Countries where that had previously been the case were observed to achieve a higher level of mutual understanding of different stakeholders, and thereby produced greater value-added.